Probabilistic resilience analysis of urban road network considering wind damage to street trees via dimension-reduced probability density evolution equation (DR-PDEE) (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
A probabilistic framework to quantify the resilience of urban road networks considering the wind blowdown of urban trees is proposed. Various properties of street patterns, including length, speed class, and width, as well as the failure probability due to tree-blowdown are considered. The resilience is considered as the mean normalized efficiency during the reconstruction period, and a reconstruction strategy based on the edge betweenness and estimated edge recovering time is employed. The probability density function (PDF) of the estimated resilience under different wind speed is computed by using the dimension-reduced probability density evolution equation (DR-PDEE). The road network of the Inner-Ring area of Yangpu district, Shanghai, China is considered as an example.